Effect of Gelling Agent and Plant Growth Regulators on In Vitro Shooting and Rooting of Stevia rebaudiana Bertoni - Ghizlane Bouaaza; Ouiam Chetto; Lhou Beniken; Laila Dziri; M’hamed Majji; Rachid Benkirane; Hamid Benyahia (Advances in Agriculture)
Stevia rebaudiana Bertoni is an economically important medicinal plant producing zero-calorie diterpenes glycosides in its leaves. This herb is a new source of natural sugar substitute, which makes it a valuable crop for the world. The growth and development of Stevia in vitro were strongly influenced by genotype, exogenous plant growth regulators (PGRs), and type of gelling agent. This study aimed to evaluate the effects of two different gelling agents (agar and gelrite) and PGRs on plant growth and multiplication of stevia. Nodal explants were placed on Murashig and Skoog (1969) (MS) medium supplemented with kinetin (KIN), indole-3-acetic acid (IAA), and 6-benzylaminopurine (BAP) and gelled with agar or gelrite for shoot proliferation. After 4 weeks, in vitro shoot segments were cultured on MS medium without any PGRs and gelled with 7 g/L of agar or 3 g/L of gélrite for rooting. Direct shoot formations were highly effective on MS medium gelled with agar. The highest number of shoots was reported for plants propagated on MS medium fortified with 0.5 mg/L of BAP + 0.5 mg/L of IAA. MS medium without any PGRs (control) produced a long shoot with the highest number of internodes. Rooting of stevia was best on an agar-gelled medium.